Complications and outcomes of trimethoprim–sulphamethoxazole as chemoprophylaxis for pneumocystis pneumonia in renal transplant recipients. Issue 3 (March 2014) - Mitsides, Nicos; Greenan, Kerry; Green, Darren; Middleton, Rachel; Lamerton, Elizabeth; Allen, Judith; Redshaw, Jane; Chadwick, Paul R; Subudhi, Chinari PK; Wood, Grahame
Abstract Background Following a pneumocystis pneumonia (PCP) outbreak in our nephrology unit, all transplant patients were offered chemoprophylaxis with trimethoprim–sulphamethoxazole (TMP‐SMX) as the first line agent. A high rate of complications was noted. We aimed to quantify TMP‐SMX associated adverse events and evaluate its prophylactic benefit in their light. Potential risk factors for complications' development were also investigated. Method This was an observational study of outcomes in transplant recipients commenced on TMP‐SMX prophylaxis for 1year period. End‐points were adverse events due to TMP‐SMX, the additional medical burden resulting from these events, and PCP diagnosis. Results 290 patients commenced on TMP‐SMX. 110 (38%) developed complications with most common being rise in serum creatinine (Cr) (n = 63, 22%) followed by gastrointestinal symptoms (n = 15, 5%), and leucopenia (n = 5, 2%). PCP incidence fell from 19 cases in 19 months to 2 cases in 12 months. Baseline renal function (P = 0.019) was an independent predictors for developing rise in Cr with TMP‐SMX. Conclusion Use of chemoprophylaxis is an effective strategy in dealing with a PCP outbreak but can lead to a high number of complications. Rises in serum Cr can cause significant concern and increase in the number of investigations.